IT Workforce Outsourcing Benefits, Challenges and Success Factors in the Customer and Supplier Perspectives - Simões, Carlos Alberto; Santos, Gleison (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2020: Anais do XIX Simpósio Brasileiro de Qualidade de Software, 2020)
Software organizations need IT workforce members with knowledge and skills to perform their activities properly. The IT workforce may be employed by the organization or made available by an external supplier. Several benefits, challenges, and success factors are associated with workforce outsourcing. They must be addressed properly as they influence directly or indirectly the performance and quality of services provided in the development and maintenance of information systems. We present a qualitative study on the benefits, challenges and success factors associated with outsourcing the IT workforce. We interviewed 38 participants involved in the IT workforce outsourcing business as contract managers, consultants, and team and workforce managers. As a result, we present 18 benefits, 67 challenges, and 31 success factors from the perspective of organizations that hire or provide outsourced workers. This study can be used to increase knowledge in the IT workforce outsourcing business, helping to identify best practices, minimize risks and support the definition and improvement processes related to IT workforce outsourcing.